Lateral incision 1-stage urethroplasty with oral mucosal graft for patients with penile urethral stricture after hypospadias repair—a preliminary report - Jianwei Wang; Xiao Xu; Zhengqing Bao; Zhenhua Liu; Guizhong Li; Feng He (BMC Urology, 2023)
Abstract Purpose To report our early experience of a novel surgical approach for penile urethral strictures after hypospadias repair, using a lateral incision to keep the ventral tissue and vasculature of the penis intact and to avoid the need for tissue interposition. Patients and methods A total of 21 patients underwent lateral incision 1-stage urethroplasty with oral mucosal graft. The median age of the patients was 21 years old (range, 13–47). The median number of prior procedures for hypospadias repair was 3 (range, 1–9) with 18 of 21 patients (85.7%) undergoing greater than 1 prior reconstructive procedure. The mean length of the penile urethral strictures was 4.5 ± 1.7 cm, with a range of 1.0 to 8.0 cm. Selection criteria for lateral incision 1-stage urethroplasty include: non-obliterative stricture, no or mild penile curvature and no urethrocutaneous fistula. Results Median follow-up was 30 months (range, 6–73). Success was achieved in 17 of 21 patients (80.9%). The 4 (19.0%) patients with treatment failure developed recurrent urethral strictures. Of the 4 men with recurrent strictures, 3 were ultimately treated successfully by DVIU (2) or two-stage urethroplasty (1), and one patient chose repeated dilation. Conclusions For patients with penile urethral stricture after hypospadias repair with non-obliterative stricture, no significant penile curvature and no urethrocutaneous fistula, a lateral approach with oral mucosal graft is a simple technique that avoids the need for tissue interposition and keeps the penile ventral tissue and vasculature intact, resulting in a low risk of complications.